2021
DOI: 10.1111/tpj.15573
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane‐localized SEM1 protein mediates sugar movement to sink rice tissues

Abstract: The translocation of photosynthate carbohydrates, such as sucrose, is critical for plant growth and crop yield. Previous studies have revealed that sugar transporters, plasmodesmata and sieve plates act as important controllers in sucrose loading into and unloading from phloem in the vascular system. However, other pivotal steps for the regulation of sucrose movement remain largely elusive. In this study, characterization of two starch excesses in mesophyll (sem) mutants and dye and sucrose export assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Callose extraction and quantification were performed as described previously (Wang et al., 2022). Seeds (0.1 g) were fixed with ethanol at 4°C for 12 h, homogenized in 1 m NaOH for 2 min and incubated at 80°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Callose extraction and quantification were performed as described previously (Wang et al., 2022). Seeds (0.1 g) were fixed with ethanol at 4°C for 12 h, homogenized in 1 m NaOH for 2 min and incubated at 80°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds (0.1 g) were ground in 1 ml of 0.1 m citric acid sodium citrate buffer (pH 5.0), and the enzyme solution was extracted according to the method described by Wang et al. (2022). The degradation reaction contained 0.2 ml of enzyme solution and 0.2 ml of 1 mg ml −1 laminarin, and was incubated at 30°C for 1 h. After adding 0.6 ml of 3,5‐dinitrosalicylic acid into the reaction, the reactions were incubated in a boiling water bath for 15 min, and then the glucose content was determined by spectrophotometry at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Stem samples from leaves or the 2nd internode were collected from rice at the heading stage. The tissues were cut to 0.5 cm and fixed in 2.5% glutaraldehyde for 12 h. The samples were prepared according to the methods of Wang et al (2022) and then imaged with a scanning electron microscope (H-7500, Hitachi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that grain filling is affected by changes in the expression of genes related to photosynthetic capacity, such as those associated with source-sink translocation ( Brazel and Ó'Maoiléidigh, 2019 ; Sanchez-Bragado et al., 2020 ; Zhang et al., 2022 ). Additionally, nutritional transport systems such as transporters of nutrient elements ( Shannon, 1972 ; Sosso et al., 2015 ; Bezrutczyk et al., 2018 ; Wang et al., 2018 ; Shen et al., 2022 ; Wang et al., 2022 ; Yang B. et al., 2022 ; Sun et al., 2023 ), plasmodesmata, and sieve plates are essential to grain filling determination ( Zhang et al., 2010 ; You et al., 2021 ). Lastly, enzymes that synthesize storage starch ( Hannah and James, 2008 ; Huang et al., 2021 ; Wang et al., 2021 ) and lipids ( Yang Y. et al., 2022 ; Luo et al., 2023 ) and genes that encode storage proteins ( Yang et al., 2023 ; Zhao et al., 2023 ) in seeds work together to determine grain yield and quality of the cereal crops.…”
mentioning
confidence: 99%